Implementasi Pendidikan Budi Pekerti Dalam Menanggulangi Kenakalan Siswa - Siti Fatimah; Nurul Zuriah; M Syahri (Jurnal Civic Hukum, 2016)
The purpose of this study is: (1) To identify and describe the implementation ofcharacter education in addressing student misbehaviour in SMP Negeri 8 Malang. (2) To identify and describe the factors that cause delinquency students in SMP Negeri 8 Malang. (3) To determine and describe the obstacles and supporting elements in the face in the implementation of character education in dealing with student misbehaviour in SMP Negeri 8 Malang. (4) To identify and describe the solutions taken by the school to address the factors inhibiting the implementation of character education in dealing with student misbehaviour inSMP Negeri 8 Malang. This study uses qualitative research techniques. Where researchers go directly into the field to gather information related to the title of the review. The data collection was obtained by interview, observation and documentation. The informant information that needs to be explored is the principal, teachers PPKn SMP Negeri 8 Malang, Islamic Teacher SMP Negeri 8 Malang, Teacher Guidance Counseling (BK) SMP Negeri 8 Malang, andinformant of class VII students of SMP Negeri 8 Malang. Based on research conducted by researchers at SMP Negeri 8 Malang The results obtained are (1) Implementation of character education in dealing with student misbehaviour in SMP Negeri 8 Malang in accordance with the Vision and Mission of SMP Negeri 8 Malang, and through all subjects and extracurricular activities through SMP Negeri 8 Malang. (2) Causes of Delinquency students occurrence due to the influence of the external environment that influences society and the mass media technology and increasingly sophisticated. (3) Obstacles and Supporting implementation of character education in dealing with student misbehaviour in SMP Negeri 8 Malang is, the inhibiting factor because fulgar outside media such as the internet and the mass media that children easy access to the things that cause the destruction of morals of the nation while the supporting factors of all components of the school is good that all the teachers and administrative staff who have been part of the support. (4) The solution in overcoming factors inhibiting the implementation of character education that is conducted by the school SMP Negeri 8 Malang is to be arranged in the system, the role of government itself must care for the child as a future asset, and there must be cooperation between all the components in schools SMP Negeri 8 Malang.